THE REALIZATION OF CLAUSE COMPLEXES IN ARTICLE ABSTRACTS - Sarip, Sri Kurnia; Hidayat, Yusuf (LPPM Universitas Bumigora Mataram, 2019)
This study reports the anaysis of taxis realized in cluase complexes of the article abstracts. The article abstracts themselves were taken from the International Seminar on Educational Technology (ISET) proceedings published by Postgraduate program, State University of Semarang. In the present study, the writers employed qualitative descriptive study such suggested by Fraenkel, Wallen, and Hyun (2012) to analyze the data. The results of the study showed that parataxis is more dominant than hypotaxis used in clause complexes in article abstracts. Those could be seen that 10% of parataxis is constructed in the text, while 8% of hypotaxis is constructed in the texts. In conclusion, the construction of parataxis is more dominant written in the article abstracts.This study reports the anaysis of taxis realized in cluase complexes of the article abstracts. The article abstracts themselves were taken from the International Seminar on Educational Technology (ISET) proceedings published by Postgraduate program, State University of Semarang. In the present study, the writers employed qualitative descriptive study such suggested by Fraenkel, Wallen, and Hyun (2012) to analyze the data. The results of the study showed that parataxis is more dominant than hypotaxis used in clause complexes in article abstracts. Those could be seen that 10% of parataxis is constructed in the text, while 8% of hypotaxis is constructed in the texts. In conclusion, the construction of parataxis is more dominant written in the article abstracts.